Professionalism Redundant, Reshaped, or Reinvigorated? Realizing the "Third Logic" in Contemporary Health Care. (September 2015) - Martin, Graham P.; Armstrong, Natalie; Aveling, Emma-Louise; Herbert, Georgia; Dixon-Woods, Mary
Recent decades have seen the influence of the professions decline. Lately, commentators have suggested a revived role for a "new" professionalism in ensuring and enhancing high-quality health care in systems dominated by market and managerial logics. The form this new professionalism might take, however, remains obscure. This article uses data from an ethnographic study of three English health care improvement projects to analyze the place, potential, and limitations of professionalism as a means of engaging clinicians in efforts to improve service quality. We found that appeals to notions of professionalism had strong support among practitioners, but converting enthusiasm for the principle of professionalism into motivation to change practice was not straightforward. Some tactics used in pursuit of this deviated sharply from traditional models of collegial social control. In systems characterized by fissures between professional groups and powerful market and managerial influences, we suggest that professionalism must interact creatively but carefully with other logics.